The Impact of Genre-Based Approach and Canva on Students’ Speaking Ability (Lembaga Pengembangan Kinerja Dosen, 2026)
This study investigates the impact of the Genre-Based Approach (GBA) and Canva as learning media in improving students’ speaking skills at SMA Negeri 12 Bandar Lampung. The participants were 70 students divided into two groups: XII KP 1.1 (control class) and XII KP 2.2 (experimental class). Both groups were given pre-tests and post-tests to assess their speaking performance using a rubric adapted from Figueras (2019), covering fluency, pronunciation, grammar, vocabulary, content, and coherence. In addition, the assessment also included genre-related indicators, namely the mastery of text structure and linguistic features. The control class, taught using conventional methods, showed an improvement in the mean score from 51.81 to 63.05, while the experimental class, taught through GBA combined with Canva, demonstrated a greater increase from 52.65 to 66.60. The paired sample t-test results confirmed that both groups experienced significant progress, yet the experimental class achieved a higher mean difference (13.95) compared to the control class (11.23). These findings suggest that the integration of GBA and Canva not only enhances students’ fluency, pronunciation, grammar, vocabulary, content, and coherence, but also improves their awareness of genre conventions and ability to construct coherent texts. Therefore, this method can be considered an effective instructional strategy to foster speaking skills in EFL classrooms.